Head identification in binominal constructions - Gomes Camacho, Roberto; Saverio Serafim, Monielly Cristina (Linguistik Online, 2021)
Determining the head of complex noun phrases is in general not an easy task in Portuguese. In the case of uma garrafa de vinho ‘a bottle of wine’, in combination with quebrou-se ‘broke’ or derramou ‘spilled’, it is the selection restrictions of the verb that determine which noun functions as head. This paper deals with a specific type of Brazilian Portuguese NP, aquele idiota do médico ‘that idiot of a doctor’, called “binominal” by Aarts (1998). The two types of nominal elements, linked by the preposition de, are the first constituent, idiota ‘idiot’, which has an evaluative status, and the second constituent, médico ‘doctor’, which has a referential status. The hypothesis defended here is that the evaluative nature of the first constituent and the referential nature of the second consist in a conclusive criterion for the determination of headedness.